Examining the ethico-legal aspects of the right to refuse treatment in Turkey - SERT, GÜRKAN (BMJ PUBLISHING GROUP, 2013)
This paper examines the ethico-legal problems regarding the right to refuse treatment in Turkey's healthcare system. We discuss these problems in the light of a recent case that was directly reported to us. We first summarise the experience of a chronically dependent patient (as recounted by her daughter) and her family during their efforts to refuse treatment and receive palliative care only. This is followed by a summary of the legal framework governing the limits of the right to refuse treatment in Turkey. With the help of this background information on the legal framework, we re-examine the ethico-legal aspects of the case and explain the underlying reasons for the problems the family and the patient experienced. Finally, we conclude that Turkey's legal framework relating to the right to refuse treatment needs to be clarified and amended in accordance with international conventions and fundamental human rights.
Keywords: Legal Aspects; Elderly and Terminally Ill; Paternalism; Right to Refuse Treatment; Autonomy